Examining Musculoskeletal Symptoms In Youths Who Participate In Athletics And Those Who Do Not: A Cross-Sectional Study (Journal of Pharmaceutical Negative Results, 2021)
Objective: The study's objective was to look into and contrast the effect and prevalence of musculoskeletal problems among teenage athletes and non-athletes. The findings may contribute to the development of rehabilitation plans and preventative actions that support musculoskeletal health in both groups, as well as the assessment of possible gender disparities.Study design : A cross-sectional study.Duration and place of study : department of orthopedic mmc mardan from 05-jan 2020 to 05-july 2020Methods:A total of 385 adolescents with mean age: 18.12± 02.22 years including 217 athletes with mean age: 19.44±01.38 years and 168 non-athlete controls mean age: 16.80 ± 01.22 were recruited for this study. Anthropometric information was taken and was examined for musculoskeletal symptoms developed over the 06-month duration using Teen Nordic Musculoskeletal Screening Questionnaire (TNMQ-S). The assessment of symptoms and the level of control of school absenteeism and physical activity was compared in the two groups.Results:A higher number of non-athlete controls reported the development of symptoms in the neck (n-171 (45.2%) compared to 93 (24.8%), upper back (157 (42.2%) compared to 75 (20.8%), and low back (161 (43.2%) compared to 131 (34.8%). B. These areas have demonstrated greater rates of physical activity and lower rate of absence from school in athletes as compared to the non-athlete group. C. Among non-athletes, there was a greater development of shoulder 138(37.1%) vs. 101(27.2%) and wrist/hand 79(23.8%) vs. 57(15.2%) symptoms. In the elbow it was 35(9.2%) vs. 36(10.2%), more prevalent in athlete group.ConclusionThis study demonstrates the differences between teenage athletes and non-athletes in the occurrence of musculoskeletal symptoms and their effects on physical activity and school attendance. The incidence of symptoms was greater in non-athlete controls, especially in the neck, upper back, and low back areas. This highlights the necessity of focused preventative and rehabilitative treatments in this population.